Food-waste anaerobic digestate as a fertilizer: The agronomic properties of untreated digestate and biochar-filtered digestate residue. (December 2021) - Song, Shuang; Lim, Jun Wei; Lee, Jonathan T.E.; Cheong, Jia Chin; Hoy, Sherilyn H.; Hu, Qiang; Tan, Jonathan K.N.; Chiam, Zhongyu; Arora, Srishti; Lum, Tiffany Q.H.; Lim, Ee Yang; Wang, Chi-Hwa; et al.
Highlights: Raw food-waste digestate and digestate-biochar residue tested as fertilizer. Digestate at 20–40% application rates performed similarly to mineral fertilizer. Digestate likely induced stress response in all 4 vegetables at concentrations >40%. Digestate application increased the relative abundance of Synergistetes. Digestate-biochar residue generally performed similarly to mineral fertilizer. Abstract: Anaerobic digestion produces large quantities of digestate as a by-product, which can potentially be applied as an organic fertilizer, but untreated anaerobic digestate (AD) may contain phytotoxins and the large volume of AD makes transportation and storage difficult. This study explored two relatively inexpensive processing methods to improve the agronomic performance of AD as a fertilizer via vegetable cultivation experiments. We first investigated the effect of dilution on AD's performance using four leafy vegetables (Chinese spinach, water spinach, Chinese cabbage and lettuce). The optimal concentrations of the AD were 20–40% (v/v in 250 mL applications per single-plant pot) for all four vegetables based on shoot fresh weight and comparable to the control treatment using commercial fertilizer. AD application also introduced Synergistetes bacteria into the growing medium, but the overall bacterial diversity and composition were similar to those of the control treatment. Considering the nutrient separation in the liquid and solid fractions of AD and the need to reduce the volume, we then experimented with the recovery of nutrients from both the liquid and solid fractions by filtering AD using two types of wood-based biochar (100 g biochar: 1 L AD) before applying the AD-biochar residues as side dressing at 1% (w/w). Both types of biochar achieved yields comparable to the treatment using a commercial fertilizer for the three vegetables tested (kale, lettuce and rocket salad). Our results show that dilution and biochar filtration can improve the agronomic performance of AD, making it a sustainable substitute for commercial fertilizer.